Nilai-nilai Sosial dalam Novel Bukan Pasar Malam Karya Pramoedya Ananta Toer - Saputra, Wahyu; Atmazaki, Atmazaki; Abdurahman, Abdurahman (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
The article focus on description and an analysis; (1) types of social moral value which reflection on novel of Bukan Pasar Malam by Pramoedya Ananta Toer; and (2) fungtion of social moral value which reflection from novel of Bukan Pasar Malam by Pramoedya Ananta Toer. This research uses qualitative methodes with descriptive method and also use objective method and mimesis. The analysis material with this description use analysis material based on type of consep and fungtion moral value, then interpretation material that we analysis based on the theory. This research include type and the fungtion moral value that reflection in novel of Bukan Pasar Malam by Pramoedya Ananta Toer is helping, love, understanding, care, togetherness, and also the fungtion of moral value as level of social, motivation, guideline, and monitoring sosial person.